The Neural Cost of the Auditory Perception of Language Switches: An Event-Related Functional Magnetic Resonance Imaging Study in Bilinguals - Abutalebi, Jubin (J Neurosci, 2007)
One of the most remarkable abilities of bilinguals is to produce and/or to perceive a switch from one language to the other without any apparent difficulty. However, several psycholinguistic studies indicate that producing, recognizing, and integrating a linguistic code different from the one in current use may entail a processing cost for the speaker/listener. Up to now, the underlying neural substrates of perceiving language switches are unknown. In the present study, we investigated the neural mechanisms of language switching during auditory perception in bilinguals. Event-related functional magnetic resonance imaging was performed in 12 early, highly proficient Italian/French bilinguals, who were more exposed to their second language. Subjects had to listen to narratives containing “switched passages” that could either respect (i.e., regular switches) or violate (i.e., irregular switches) the constituents of sentence structure. The results indicate that switching engages an extensive neural network, including bilateral prefrontal and temporal associative regions. Moreover, a clear dissociation is observed for the types of switches. Regular switches entail a pattern of brain activity closely related to lexical processing, whereas irregular switches engage brain structures involved in syntactic and phonological aspects of language processing. Noteworthy, when switching into the less-exposed language, we observed the selective engagement of subcortical structures and of the anterior cingulate cortex, putatively involved in cognitive and executive control. This suggests that switching into a less-exposed language requires controlled processing resources. This pattern of brain activity may constitute an important neural signature of language dominance in bilinguals.